Association between Bone Morphogenetic Protein 2 Gene Polymorphisms and Skeletal Fluorosis of The Brick-tea Type Fluorosis in Tibetans and Kazakhs, China. Issue 7 (3rd July 2022) - Lou, Qun; Guo, Ning; Huang, Wei; Wu, Liaowei; Su, Mengyao; Liu, Yang; Liu, Xiaona; Li, Bingyun; Yang, Yanmei; Gao, Yanhui
ABSTRACT: To investigate the potential association between BMP2 single nucleotide polymorphisms (SNPs) and brick-tea-type skeletal fluorosis risk in cross-sectional case-control study conducted in Sinkiang and Qinghai, China, a total of 598 individuals, including 308 Tibetans and 290 Kazakhs, were enrolled. Using the standard WS/192-2008 (China), 221 skeletal fluorosis cases were diagnosed, including 123 Tibetans and 98 Kazakhs. Logistic regressions 2 analysis did not find the association between SNPs (Rs235764, Rs235739 and Rs996544) and skeletal fluorosis. Genetic models, linkage disequilibrium (LD) and haplotype analysis were not found to be associated with risk of skeletal fluorosis after adjustment by age and sex (P>0.05).Our data suggested that Rs 235764, Rs 235739 and Rs 996544 were not linked susceptibility for skeletal fluorosis in our cross-sectional case–control study.